Exploring Students' Multifaceted Engagement with Academic Results: Insights from Secondary School Certificate (SSC) (Global Journal of Human-Social Science, 2026)
Secondary School Certificate (SSC) level students have high expectations of achieving the best results, so they put in their best efforts to achieve the highest possible outcomes. The main objective of this study was to examine the nature of students' engagements and related activities in relation to their academic results. Data were collected using the tools and techniques of the social survey method. A structured questionnaire including both closed-ended and open-ended questions was employed for data collection. Data were collected from a total of 105 respondents. The majority of the respondents expressed satisfaction with their academic results. The research findings reveal that, in pursuit of better academic outcomes, students beyond regular school attendance actively participate in private tutoring, coaching centres, and other learning opportunities available to them. Engagement in private tuition and coaching entails significant financial costs. Furthermore, parents, close relatives, friends, and acquaintances closely keep an eye on students' academic progress and results. In the past, examination results were typically known only to the students themselves and their parents. However, a much wider circle of involvement is now observed. Whereas students previously shared their results primarily with their parents, they now share this information to multiple individuals. These practices reflect the multifaceted nature of students' engagement with academic achievement in contemporary era.